Biological piezoelectric ceramic as well as preparation method and application thereof

By compounding HA with BNT or BNKLT and doping potassium and lithium ions, HA/BNT or HA/BNKLT biopiezoelectric ceramics are prepared, which solves the toxicity problems of elements such as barium and niobium in existing biopiezoelectric ceramics and the problem of bulky driving power supply, and improves biodegradation and piezoelectric performance, and meets the self-powering needs of implantable biodegradable sensors.

CN119528565APending Publication Date: 2025-02-28SHANGHAI GEFITE SENSOR TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411617703.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing biopiezoelectric ceramics are used in biological bodies that have ions such as barium and niobium are toxic to the organism, leading to potential cytotoxicity problems, and the driving power supply is bulky, which limits its implantation and use in biological bodies.

Method used

The bioceramic material HA is compounded with lead-free piezoelectric ceramics sodium bismuth titanate (Bi0.5Na0.5TiO3, referred to as BNT) or BNKLT to prepare HA/BNT or HA/BNKLT biopiezoelectric ceramics, and doped with a certain amount of potassium and lithium ions to improve biodegradation and piezoelectric properties.

Benefits of technology

The obtained HA/BNT biopiezoelectric ceramics exhibit significant biodegradable properties and certain piezoelectric properties, which can meet the self-powering needs of implantable biodegradable sensors, while avoiding the toxicity problems of elements such as barium and niobium. By doping potassium and lithium ions, the piezoelectric performance of HA/BNKLT biopiezoelectric ceramics is further improved, meeting the needs of sensor driving power supply.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528565A_ABST
    Figure CN119528565A_ABST
Patent Text Reader

Abstract

The invention discloses biological piezoelectric ceramic as well as a preparation method and application thereof, and belongs to the field of implantable and biodegradable sensor materials. A biological ceramic material hydroxyapatite (HA) and a lead-free piezoelectric ceramic material sodium bismuth titanate (BNT) are compounded, the obtained HA / BNT biological piezoelectric ceramic shows remarkable biodegradability and certain piezoelectric property, and a certain amount of potassium and lithium ions are further doped in BNT, so that the biodegradability of the HA / BNT biological piezoelectric ceramic is improved, and the biodegradability of the HA / BNT biological piezoelectric ceramic is improved. The obtained HA / BNKLT biological piezoelectric ceramic also shows remarkable biodegradability and certain piezoelectric property, and the two kinds of biological piezoelectric ceramics can meet the self-power supply requirement of an implantable biodegradable sensor. In addition, the biological piezoelectric ceramic provided by the invention can avoid the potential toxicity problem caused by barium ions and niobium ions in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a biological piezoelectric ceramic and a preparation method and application thereof, belonging to the field of implantable biodegradable sensor materials. Background Art

[0002] In recent years, with the increasing number and frequency of electronic devices, the environmental pollution caused by non-degradable electronic device waste has gradually emerged. In the medical field, compared with traditional implantable sensors, implantable biodegradable sensors (Biodegradable Sensor, referred to as BD-SEN) have the advantage of being degradable in the body and do not require secondary surgery to remove. On the one hand, it avoids the risk of infection and secondary injury, and on the other hand, it avoids the pollution caused by electronic device waste, thus attracting great attention. However, the current driving power supply of BD-SEN is too bulky, which limits its implantation and use in the body. Compounding lead-free piezoelectric ceramics in bioceramics can obtain piezoelectric properties through piezoelectric ceramics under the premise of ensuring biocompatibility, and convert the mechanical energy generated by activities such as cell migration and human movement into electrical energy, which is expected to solve the self-power supply problem of BD-SEN without using an oversized or overweight driving power supply, and realize its use in the body.

[0003] The biopiezoelectric ceramics currently being developed are mainly designed to meet the needs of actual clinical applications in bone repair. It utilizes the piezoelectric effect in human bones, uses bioelectrically active piezoelectric ceramics as bone implants to convert the stress on the bone into electrical signals on the bone surface, and regulates bone metabolism and growth through electrical signals. Biopiezoelectric ceramics mainly use hydroxyapatite (Ca2+) with good biocompatibility and bioactivity. 10 (PO4)6(OH)2, referred to as HA) bioceramics are composited with lead-free piezoelectric ceramics with good piezoelectric properties. Barium titanate (BaTiO3, referred to as BT) is the most representative of lead-free piezoelectric ceramics. Many studies have used it as the piezoelectric phase in biopiezoelectric ceramics. The most reported biopiezoelectric ceramics are HA / BT composited with HA and BT. HA / BT biopiezoelectric ceramics have good biological activity. Relying on the piezoelectric properties of BT, HA / BT biopiezoelectric ceramics also have piezoelectric effect and bone bonding ability, which can promote the repair of bone defects and have broad application prospects in the field of bone repair or bone replacement medicine.

[0004] BaTiO3 is used as the piezoelectric phase in biopiezoelectric ceramics. When the BaTiO3 content is higher than 70wt%, the obtained HA / BT biopiezoelectric ceramics have good biodegradability and piezoelectric effects. However, barium ions are biotoxic, which will cause certain safety hazards in the application of HA / BT biopiezoelectric ceramics prepared with BaTiO3 in the human body (Wang Chu. Preparation and performance research of HA-BT biopiezoelectric composite materials. Master. Shaanxi University of Science and Technology, 2023). At present, the useful rare earth element Nd 3+ and Er 3+ BaTiO3 is doped in an attempt to reduce the Ba content in biopiezoelectric ceramics, but the toxicity of rare earth in rare earth-doped BaTiO3 is still unclear (Wu Cong. Research on doping modification and performance of BaTiO3 / HA composite bionic piezoelectric ceramics. Master. Xi'an University of Technology, 2016); KNN piezoelectric ceramics are also doped with Li, an element beneficial to the human body, to obtain Li-doped modified lithium sodium potassium niobate (LNK) ceramics, but niobium (Nb) ions have certain cytotoxicity to organisms, limiting their application as a driving power source in implantable biodegradable sensors (Ji Jun. New lithium sodium potassium niobate biodegradable sensor Preparation and performance research of biopiezoelectric ceramics. Master. Jiangsu University, 2017); there are also copper-doped KNN biopiezoelectric ceramics that inhibit tumor cell proliferation by regulating the endogenous electric field, thereby eliminating the infection around the implanted material (Zhai Jinxia. Research on electrical signal responsive potassium sodium niobate-based implant materials and their biological properties. Doctor. South China University of Technology, 2020); the main problem with current biopiezoelectric ceramics is that ions of elements such as barium and niobium have certain cytotoxicity to organisms. Therefore, it is urgent to study a biopiezoelectric ceramic that can guarantee self-power supply needs, has good degradation effects, and does not contain ions that are toxic to organisms. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention proposes to combine the bioceramic material HA with the lead-free piezoelectric ceramic sodium bismuth titanate (Bi 0.5 Na 0.5 TiO3, referred to as BNT) or BNKLT are compounded to prepare HA / BNT or HA / BNKLT biopiezoelectric ceramics. BNT can generate bone-like apatite on the surface after polarization. The biological activity experiment shows that BNT has no cytotoxicity and the ions it contains are safer for organisms. Further doping with a certain amount of potassium and lithium ions, the obtained HA / BNKLT biopiezoelectric ceramics also show significant biodegradability and certain piezoelectric properties.

[0006] In order to achieve the above technical objectives, the present invention provides the following technical solutions:

[0007] The present invention first provides a method for preparing a biopiezoelectric ceramic, the method comprising the following steps:

[0008] The piezoelectric ceramic material and HA powder are ball-milled and mixed in different proportions, the obtained mixture is dried and sieved, dry-pressed and then sintered at high temperature to obtain bio-piezoelectric ceramics, wherein the piezoelectric ceramic material includes BNT or BNKLT.

[0009] Furthermore, the mass percentage of the piezoelectric ceramic material in the mixture of the piezoelectric ceramic material and the HA powder is 30-90wt%.

[0010] Furthermore, the medium for ball milling mixing is deionized water and zirconia balls, and the mass ratio of the deionized water to the zirconia balls is 13:15.

[0011] Furthermore, the ball milling mixing condition is: 300r / min ball milling for 8h.

[0012] Furthermore, the dry pressing pressure is 240 MPa.

[0013] Furthermore, the sintering condition is: sintering at 1000-1300°C for 0.5-3h; preferably, the sintering condition is: sintering at 1200°C for 2h.

[0014] Wherein, the preparation method of the BNT powder is as follows:

[0015] (1) Bi2O3, Na2CO3 and TiO2 are used as raw materials and ball-milled to mix them uniformly to obtain a mixture.

[0016] (2) The ground mixture is subjected to a solid phase reaction method to prepare BNT powder. The solid phase reaction product is ball-milled for a second time, dried and sieved to obtain BNT powder.

[0017] Furthermore, the mass ratio of Bi2O3, Na2CO3 and TiO2 in step (1) is 55:15:38;

[0018] The conditions of the solid phase reaction in step (2) are: 900° C. for 2 h.

[0019] The ball milling conditions are: 300 r / min for 8 h.

[0020] The preparation method of the BNKLT powder is as follows:

[0021] (1) Bi2O3, Na2CO3, K2CO3, Li2CO3 and TiO2 are used as raw materials and ball-milled to mix them uniformly to obtain a mixture.

[0022] (2) The ground mixture is subjected to a solid phase reaction method to prepare BNT powder. The solid phase reaction product is ball-milled for a second time, dried and sieved to obtain BNT powder.

[0023] Furthermore, the mass ratio of Bi2O3, Na2CO3, K2CO3, Li2CO3 and TiO2 in step (1) is 55:10:4:1:38;

[0024] The conditions of the solid phase reaction in step (2) are: 900° C. for 2 h.

[0025] The ball milling conditions are: 300 r / min for 8 h.

[0026] The present invention also provides a bio-piezoelectric ceramic prepared by the bio-piezoelectric ceramic preparation method.

[0027] The polarization of the bio-piezoelectric ceramic comprises the following steps: screen printing silver paste on the upper and lower surfaces of the bio-piezoelectric ceramic, firing the silver electrode to obtain the silver electrode, and passing a direct current electric field in silicone oil for polarization.

[0028] The present invention also provides application of the bio-piezoelectric ceramic in preparing an implantable biodegradable sensor.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention composites the bioceramic material HA with the lead-free piezoelectric ceramic BNT or BNKLT, wherein the Bi ions, Ti ions, K ions, Li ions, etc. contained therein are non-toxic, thereby effectively avoiding the problem that BT and KNN-based biopiezoelectric ceramics contain toxic barium ions and niobium ions, thereby further avoiding the potential cytotoxicity problem of the biopiezoelectric ceramics during use.

[0031] (2) The biopiezoelectric ceramic HA / BNT obtained by the present invention exhibits significant biodegradability (22.27%) and certain piezoelectric properties (2.7 pC / N), which can meet the self-powering requirements of some implantable biodegradable sensors.

[0032] (3) The doping of elements such as potassium and lithium further improves the piezoelectric properties of biopiezoelectric ceramics. When the proportion of BNKLT is 90%, the piezoelectric performance can reach 3.8pC / N. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD diagram of the BNT powder synthesized by the solid phase reaction method in Example 1.

[0034] Figure 2 Graph showing the piezoelectric properties of the HA / BNT ceramics prepared in Examples 1-4.

[0035] Figure 3 Graph showing the biodegradability of the HA / BNT ceramics prepared in Examples 1-4.

[0036] Figure 4 Graph showing the piezoelectric performance of the HA / BNKLT biopiezoelectric ceramics prepared in Examples 5-6.

[0037] Figure 5 This is a graph showing the biodegradation performance of the HA / BNKLT biopiezoelectric ceramics prepared in Examples 5-6. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred embodiments of the present invention are described in detail below, but the following embodiments do not limit the protection scope of the present invention.

[0039] In the embodiments of the present invention, those that are not described in detail are all completed by conventional experimental methods. Those processes involved in the embodiments that are not described in detail are all understandable and easily implementable by those skilled in the art based on the product instructions or basic knowledge in the field, and therefore are not described in detail.

[0040] The chemicals involved in the following examples are all known and commonly used materials and can be purchased through conventional channels.

[0041] Embodiment 1:

[0042] Using analytically pure Bi2O3 55g, Na2CO3 15g and TiO2 38g as raw materials, BNT powder was prepared by solid phase reaction method. The specific steps are as follows: First, the raw materials are weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water is added, 150g of zirconium oxide balls are weighed as ball milling media, and ball milled for 8 hours at 300r / min using a planetary mill. After drying and grinding, the slurry is solid-phase reacted at 900°C for 2 hours, and the obtained product is ball-milled for a second time at 300r / min for 8 hours, dried and sieved to obtain BNT powder, and its phase XRD spectrum is shown as follows. Figure 1 As shown, it is shown that the synthetic powder is indeed BNT.

[0043] 35g of BNT powder synthesized by solid phase reaction and 15g of analytically pure HA powder were mixed in proportion using a planetary ball mill, 65g of deionized water was added, and 75g of zirconium oxide balls were weighed as ball milling media to prepare HA / BNT composite powder with a BNT content of 70wt% (referred to as HA-70BNT). After drying, sieving and granulating the composite powder, it was dry-pressed into a round sample at 240MPa, and HA-70BNT was fired at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm and a thickness of about 1mm after firing. After screen printing silver paste on its upper and lower surfaces, the electrode was fired at 750℃. Then it was placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0044] The piezoelectric constant of HA-70BNT biopiezoelectric ceramic is 0.5pC / N, and the mass loss rate is 32.92% after immersion in simulated body fluid at 37°C for 14 days. It shows significant biodegradability and certain piezoelectric properties, which can meet the self-powering requirements of some implantable biodegradable sensors.

[0045] Embodiment 2:

[0046] 55g of analytically pure Bi2O3, 15g of Na2CO3 and 38g of TiO2 were used as raw materials to prepare BNT powder by solid phase reaction method. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for 8 hours at 300r / min for a second time, and then dried and sieved to obtain BNT powder. XRD analysis showed that the phase was BNT.

[0047] Use a planetary mill to mix 45g of BNT powder synthesized by solid phase reaction and 5g of analytically pure HA powder in proportion, add 65g of deionized water, and weigh 75g of zirconium oxide balls as ball milling media to prepare HA / BNT composite powder with a BNT content of 90wt% (referred to as HA-90BNT). After drying, sieving and granulating the composite powder, it is dry-pressed into a circular sample at 240MPa, and HA-90BNT is fired at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm after firing and a thickness of about 1mm. After screen printing silver paste on its upper and lower surfaces, the electrode is fired at 750℃. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0048] The piezoelectric constant of HA-90BNT biopiezoelectric ceramics is 2.7pC / N, and the mass loss rate after immersion in simulated body fluid at 37°C for 14 days is 22.27%, showing significant biodegradability and certain piezoelectric properties. Compared with HA-70BNT biopiezoelectric ceramics, the piezoelectric properties are improved. It can meet the self-powered needs of some implantable biodegradable sensors.

[0049] Embodiment 3:

[0050] 55g of analytically pure Bi2O3, 15g of Na2CO3 and 38g of TiO2 were used as raw materials to prepare BNT powder by solid phase reaction method. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for 8 hours at 300r / min for a second time, and then dried and sieved to obtain BNT powder. XRD analysis showed that the phase was BNT.

[0051] Use a planetary mill to mix 25g of BNT powder synthesized by solid phase reaction and 25g of analytically pure HA powder in proportion, add 65g of deionized water, and weigh 75g of zirconium oxide balls as ball milling media to prepare HA / BNT composite powder with a BNT content of 50wt% (referred to as HA-50BNT). After drying, sieving and granulating the composite powder, it is dry-pressed into a circular sample at 240MPa, and HA-50BNT is fired at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm and a thickness of about 1mm after firing. After screen printing silver paste on its upper and lower surfaces, the electrode is fired at 750℃. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0052] The prepared HA-50BNT biopiezoelectric ceramics have a low content of BNT piezoelectric phase and the piezoelectric constant cannot be measured. The mass loss rate after immersion in simulated body fluid at 37°C for 14 days is 5.25%, and the biodegradation effect is poor.

[0053] Embodiment 4:

[0054] 55g of analytically pure Bi2O3, 15g of Na2CO3 and 38g of TiO2 were used as raw materials to prepare BNT powder by solid phase reaction method. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for 8 hours at 300r / min for a second time, and then dried and sieved to obtain BNT powder. XRD analysis showed that the phase was BNT.

[0055] Use a planetary mill to mix 15g of BNT powder synthesized by solid phase reaction with 35g of analytically pure HA powder in proportion, add 65g of deionized water, and weigh 75g of zirconium oxide balls as ball milling media to prepare HA / BNT composite powder with a BNT content of 30wt% (referred to as HA-30BNT). After drying, sieving and granulating the composite powder, it is dry-pressed into a circular sample at 240MPa, and HA-30BNT is fired at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm after firing and a thickness of about 1mm. After screen printing silver paste on its upper and lower surfaces, the electrode is fired at 750℃. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0056] The content of BNT piezoelectric phase in the prepared HA-30BNT biopiezoelectric ceramics is very small, and the piezoelectric constant cannot be measured. The mass loss rate after immersion in simulated body fluid at 37°C for 14 days is 18.30%, and the biodegradation effect is good.

[0057] Embodiment 5:

[0058] BNKLT powder was prepared by solid phase reaction method using analytically pure Bi2O3 55g, Na2CO3 10g, K2CO3 4g, Li2CO3 1g and TiO2 38g as raw materials. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for a second time for 8 hours, dried and sieved to obtain BNKLT powder.

[0059] 45g of BNKLT powder synthesized by solid phase reaction and 5g of analytically pure HA powder were ball-milled in proportion using a planetary mill, 65g of deionized water and 75g of zirconium oxide balls were added as ball-milling media to prepare HA / BNKLT composite powder with a BNKLT content of 90wt% (referred to as HA-90BNKLT). After drying, sieving and granulating the composite powder, it was dry-pressed into a circular sample at 240MPa, and HA-90BNKLT was fired at 1200℃ for 2h. The sample used for piezoelectric performance testing had a diameter of 14mm and a thickness of about 1mm after firing. After screen-printing silver paste on its upper and lower surfaces, the electrode was fired at 750℃. It was then placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0060] The piezoelectric constant of HA-90BNKLT biopiezoelectric ceramics is 3.8pC / N, and the mass loss rate is 8.07% after immersion in simulated body fluid at 37°C for 14 days, showing good piezoelectric effect, but poor biodegradability.

[0061] Embodiment 6:

[0062] BNKLT powder was prepared by solid phase reaction method using analytically pure Bi2O3 55g, Na2CO3 10g, K2CO3 4g, Li2CO3 1g, and TiO2 38g as raw materials. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for a second time for 8 hours, dried and sieved to obtain BNKLT powder.

[0063] Use a planetary mill to mix 35g of BNKLT powder synthesized by solid phase reaction with 15g of analytically pure HA powder in proportion, add 65g of deionized water, and weigh 75g of zirconium oxide balls as ball milling media to prepare HA / BNKLT composite powder with a BNKLT content of 70wt% (referred to as HA-70BNKLT). After drying, sieving and granulating the composite powder, it is dry-pressed into a circular sample at 240MPa and sintered at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm and a thickness of about 1mm after sintering. After screen printing silver paste on its upper and lower surfaces, it is fired at 750℃ to obtain an electrode. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0064] The piezoelectric constant of HA-70BNKLT biopiezoelectric ceramics is 1.4pC / N, and the mass loss rate after immersion in simulated body fluid at 37°C for 14 days is 10.62%. The doping of K and Li ions effectively improves the piezoelectric properties of biopiezoelectric ceramics. When the BNKLT content is 70wt%, HA / BNKLT biopiezoelectric ceramics show good piezoelectric effect and good biodegradation effect. It can meet the self-powered needs of some implantable biodegradable sensors.

[0065] Embodiment 7:

[0066] BNKLT powder was prepared by solid phase reaction method using analytically pure Bi2O3 55g, Na2CO3 10g, K2CO3 4g, Li2CO3 1g, and TiO2 38g as raw materials. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for a second time for 8 hours, dried and sieved to obtain BNKLT powder.

[0067] Use a planetary mill to mix 25g of BNKLT powder synthesized by solid phase reaction and 25g of analytically pure HA powder in proportion, add 65g of deionized water, and weigh 75g of zirconium oxide balls as ball milling media to prepare HA / BNKLT composite powder with a BNKLT content of 50wt% (referred to as HA-50BNKLT). After drying, sieving and granulating the composite powder, it is dry-pressed into a circular sample at 240MPa and sintered at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm and a thickness of about 1mm after sintering. After screen printing silver paste on its upper and lower surfaces, it is fired at 750℃ to obtain an electrode. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0068] The piezoelectric constant of HA-50BNKLT biopiezoelectric ceramics is 0.5pC / N, and the mass loss rate after immersion in simulated body fluid at 37°C for 14 days is 6.66%. The doping of K and Li ions effectively improves the piezoelectric properties of biopiezoelectric ceramics. When the BNKLT content is 50wt%, HA / BNKLT biopiezoelectric ceramics show good piezoelectric effect and good biodegradation effect. It can meet the self-powered needs of some implantable biodegradable sensors.

[0069] Embodiment 8:

[0070] BNKLT powder was prepared by solid phase reaction method using analytically pure Bi2O3 55g, Na2CO3 10g, K2CO3 4g, Li2CO3 1g, and TiO2 38g as raw materials. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for a second time for 8 hours, dried and sieved to obtain BNKLT powder.

[0071] Use a planetary mill to mix 15g of BNKLT powder synthesized by solid phase reaction with 35g of analytically pure HA powder in proportion, add 65g of deionized water, and weigh 75g of zirconium oxide balls as ball milling media to prepare HA / BNKLT composite powder with a BNKLT content of 30wt% (referred to as HA-30BNKLT). After drying, sieving and granulating the composite powder, it is dry-pressed into a circular sample at 240MPa and sintered at 1200℃ for 2h. The sample used for piezoelectric performance testing has a diameter of 14mm and a thickness of about 1mm after sintering. After screen printing silver paste on its upper and lower surfaces, it is fired at 750℃ to obtain an electrode. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0072] The piezoelectric constant of HA-30BNKLT biopiezoelectric ceramics could not be detected, and the mass loss rate after immersion in simulated body fluid at 37°C for 14 days was 11.95%. When the BNKLT content was 30wt%, HA / BNKLT biopiezoelectric ceramics showed good biodegradability.

[0073] Comparative Example 1:

[0074] Weigh 50g of analytically pure HA powder, sieve and granulate it, then dry press it into a round sample at 240MPa, and sinter it at 1200℃ for 2h. The diameter of the sample after sintering is 14mm and the thickness is about 1mm.

[0075] The mass loss rate of HA bioceramics after immersion in simulated body fluid at 37°C for 14 days was 11.02%.

[0076] Comparative Example 2:

[0077] 55g of analytically pure Bi2O3, 15g of Na2CO3 and 38g of TiO2 were used as raw materials to prepare BNT powder by solid phase reaction method. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for 8 hours at 300r / min for a second time, and then dried and sieved to obtain BNT powder. XRD analysis showed that the phase was BNT.

[0078] Weigh 50g of BNT powder synthesized by solid phase reaction method, sieve and granulate, dry press into round samples at 240MPa, and sinter at 1200℃ for 2h. The diameter of the sample used for piezoelectric performance test after sintering is 14mm and the thickness is about 1mm. After screen printing silver paste on the upper and lower surfaces, the electrode is sintered at 750℃. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0079] The piezoelectric constant of BNT piezoelectric ceramics is 62pC / N.

[0080] Comparative Example 3:

[0081] BNKLT powder was prepared by solid phase reaction method using analytically pure Bi2O3 55g, Na2CO3 10g, K2CO3 4g, Li2CO3 1g, and TiO2 38g as raw materials. The specific steps are as follows: First, the raw materials were weighed according to the stoichiometric ratio and placed in a resin tank, 130g of deionized water was added, 150g of zirconium oxide balls were weighed as ball milling media, and the mixture was ball milled at 300r / min for 8 hours using a planetary mill. After drying and grinding, the slurry was solid phase reacted at 900℃ for 2 hours, and the obtained product was ball milled for 8 hours at 300r / min for a second time, and then dried and sieved to obtain BNKLT powder.

[0082] Weigh 50g of BNKLT powder synthesized by solid phase reaction method, sieve and granulate, dry press to form a round sample at 240MPa, and sinter at 1200℃ for 2h. The diameter of the sample used for piezoelectric performance test after sintering is 14mm and the thickness is about 1mm. After screen printing silver paste on the upper and lower surfaces, the electrode is sintered at 750℃. Then it is placed in 80℃ silicone oil and polarized with a DC electric field of 4.5kV / mm for 20min.

[0083] The piezoelectric constant of BNKLT piezoelectric ceramics is 92pC / N.

[0084] Biodegradation experiment:

[0085] The sample was soaked in simulated body fluid (SBF) at 37°C. Each sample (Φ10mm, 2mm thick) required 20mLSBF for each soaking, and the SBF was replaced every 2 days. The initial mass of the sample was weighed before the biodegradation experiment, as well as the mass of the sample after soaking in SBF for 1, 3, 5, 7, 10, and 14 days. The specific process was as follows: the sample was taken out of SBF, the constant temperature water bath was closed, the SBF was poured out, 40mL of deionized water was added, and the sample was shaken twice. The sample was placed in a constant temperature oven at 140°C for drying until the mass did not change, and its mass was weighed. The mass loss rate was calculated to evaluate its biodegradability.

[0086] Ions and their concentrations in SBF: Na + 142mol / L, K + 5mol / L、Mg 2+ 1.5mol / L, Ca 2+ 2.5mol / L, Cl - 103mol / L, HCO 3- 10mol / L, HPO4 2- 1mol / L, SO4 2- 0.5mol / L.

[0087] The samples include materials obtained in Comparative Examples 1-3 and materials obtained in Examples 1-8.

[0088] Table 1. Comparison of piezoelectric properties and biodegradability

[0089]

[0090] In summary, the present invention designs and prepares a HA / BNT biopiezoelectric ceramic, and the obtained HA / BNT biopiezoelectric ceramic exhibits significant biodegradability and certain piezoelectric properties, which can meet the self-power supply requirements of implantable biodegradable sensors. Moreover, the HA / BNT biopiezoelectric ceramic provided by the present invention degrades slowly in the first 7 days in the body, and the degradation rate gradually increases after 7 days, which meets the requirements of being used as the driving power supply part of the sensor in the human body, that is, supplying power for a period of time and gradually degrading in the body after the working life ends ( Figure 3 ). By doping a certain amount of potassium and lithium ions on the basis of HA / BNT biopiezoelectric ceramics, the piezoelectric properties of the obtained HA / BNKLT biopiezoelectric ceramics can be further improved; and HA / BNKLT biopiezoelectric ceramics also meet the requirements of being used as the driving power supply for sensors in the human body, that is, supplying power for a period of time and gradually degrading in the body after the working life ends ( Figure 5). At the same time, the HA / BNT biopiezoelectric ceramics and HA / BNKLT biopiezoelectric ceramics obtained by the present invention also avoid the potential toxicity problem caused by the introduction of barium ions and niobium ions into existing BT system and KNN system ceramics.

[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the attached embodiments and their equivalents.

Claims

1. A method for preparing a biopiezoelectric ceramic, characterized in that: The method comprises the following steps: The piezoelectric ceramic material and HA powder are ball-milled and mixed in different proportions, the obtained mixture is dried and sieved, then dry-pressed and sintered at high temperature to obtain bio-piezoelectric ceramics, wherein the piezoelectric ceramic material includes BNT powder or BNKLT powder.

2. The method for preparing the biopiezoelectric ceramic according to claim 1, characterized in that: The mass percentage of the piezoelectric ceramic material in the mixture of the piezoelectric ceramic material and the HA powder is 30-90wt%.

3. The method for preparing the biopiezoelectric ceramic according to claim 1, characterized in that: The ball milling mixing medium is deionized water and zirconium oxide balls, and the mass ratio of the deionized water to the zirconium oxide balls is 13:

15.

4. The method for preparing the biopiezoelectric ceramic according to claim 1, characterized in that: The ball milling mixing condition is: 300r / min ball milling for 8h.

5. The method for preparing the biopiezoelectric ceramic according to claim 1, characterized in that: The dry pressing pressure is 240 MPa.

6. The method for preparing the biopiezoelectric ceramic according to claim 1, characterized in that: The sintering conditions are: sintering at 1000-1300° C. for 0.5-3 h; preferably, the sintering conditions are: sintering at 1200° C. for 2 h.

7. The biopiezoelectric ceramic prepared by the method for preparing the biopiezoelectric ceramic according to any one of claims 1 to 6.

8. Use of the biopiezoelectric ceramic prepared by the preparation method of the biopiezoelectric ceramic according to any one of claims 1 to 6, or the biopiezoelectric ceramic according to claim 7 in the preparation of an implantable biodegradable sensor.

Citation Information

Cited By

  • Novel piezoelectric bionic HA / Col bone repair material with single orientation and preparation method thereof

    CN121313960A